Role of Triphala in dentistry - Shobha Prakash; Anup U Shelke (Journal of Indian Society of Periodontology, 2014)
Ayurveda is considered as the "science of life," because the ancient Indian system of health care focused views of man and his illness. India has an age-old heritage of traditional herbal medicine. Conventional drugs usually provide effective antibiotic therapy for bacterial infections, but there is an increasing problem of antibiotic resistance and a continuing need for new solutions. Hence, now herbal drugs are being preferred to synthetic antibiotics. ′Triphala′ is a well-known powdered preparation in the Indian system of medicine (ISM). It consists of equal parts of the Emblica officinalis, Terminalia chebula, and Terminalia belerica. Currently, Triphala is being extensively researched for its various therapeutic effects including its anti-caries, antioxidant, anti-collagenase, and anti-microbial activities. The present review will focus on the comprehensive appraisal of Triphala and its several applications in dentistry.